Increase in non-transferrin bound iron and the oxidative stress status in epilepsy patients treated using valproic acid monotherapy - Ounjaijean S. (2014)
Objective: This study aims to investigate the alteration of iron homeostasis and oxidative stress status in epilepsy patients treated with valproic acid (VPA) monotherapy. Materials: 24 epilepsy patients receiving VPA monotherapy (12 men, 12 women, age 27.5 ± 7.2 y) and 24 sex- and age-matched healthy volunteers were included in the study. Methods: The level of iron status parameters; serumiron, ferritin, transferrin saturation, non-transferrin bound iron (NTBI), serum level of trace elements (copper, zinc and selenium), concentration of antioxidant parameters, activities of antioxidant enzymes and level of lipid peroxidation product were determined. Results: NTBI was found in the patients although their other iron status parameters were normal. Levels of antioxidant parameters were decreased while activities of antioxidant enzymes were increased. Levels of serum MDA were significantly increased in patientswith epilepsy. The daily dose of valproic acid associatedwas statistically significant: serumconcentration of NTBI (r = 0.579; p = 0.003) and MDA (r = 0.465; p = 0.022).Apositive correlation existed between NTBI and zinc (r = 0.522; p = 0.009). Conclusion: According to our results, VPA treatment in patients with epilepsy contributes to themetabolism of iron, leading to the formation of NTBI and an increase in oxidative stress. ©2011 Dustri-Verlag Dr. K. Feistle.